Analisis Yuridis dan Etis Kasus Suap Penyidik KPK: Studi Kasus AKP Stepanus Robin Pattuju - Nikita Putri, Dhea; Purba, Lilis (Postulat, 2026)
A significant new standard has been established in the battle against corruption in Indonesia as a result of the corruption case that involves AKP Stepanus Robin Pattuju, an investigator for the Corruption Eradication Commission (KPK). Based on the ruling of the Central Jakarta Corruption Court Number 66/Pid.Sus-TPK/2021/PN.Jkt.Pst, the purpose of this publication is to conduct an analysis of the legal, ethical, and institutional elements of the case. The research employs a case-based methodology in conjunction with a normative legal strategy. Using Article 12 letter a and Article 11 of the Corruption Eradication Law in combination with Article 65 of the Criminal Code, the findings of the research demonstrate that the crime of bribery was demonstrated lawfully and persuasively. This was done in line with the law intended to eradicate corruption. From an ethical perspective, Robin's actions undermine the integrity of the KPK as an independent institution. From an institutional perspective, this case reveals the weakness of the internal oversight system and the KPK's dependence on investigators from the National Police. The main recommendations are strengthening the integrity of investigators, reforming the KPK's institutional structure, and improving the internal oversight system to prevent similar cases.